Analysis of conventional and digital (digora) radiographic methods for - Canova, Giovana C.; de Oliveira, Rodrigo C.; Carneiro, Everdan; da Silva, Renato M.; Brunini, Sérgio H. S.; Letra, Ariadne M. G.; Tavano, Orivaldo; Bramante, Clovis M.; Pereira, José C.; Granjeiro, José M. (Brazilian Dental Science, 2010)
The purpose of this study was to test the hypothesis that the digital radiographic method (Digora), when compared to the conventional radiographic method, allows better identification of the mineralized tissue barrier formed after pulpotomy in dogs and protection of the remaining pulp with a resorbable membrane of demineralized bovine cortical bone (Group I) and calcium hydroxide (Group II). Two dogs were used, according to the International Organization for Standardization, specification #7405:1997: one for a follow-up period of 7 days and another for the 70–day period. Ten teeth of each dog were submitted to pulpotomy, being 7 for Group I and 3 for Group II, resulting in sixteen treated roots for each period. Standardized procedures were used to obtain and analyze the conventional and digital radiographs. Radiographic images suggesting a mineralized barrier were only distinguished in the roots treated with calcium hydroxide; however, no agreement was achieved between four experienced observers. Concerning the comparison between the digital and conventional methods, a suggestive image of a mineralized barrier was observed in four and five roots, respectively, but only one such root belonged to the follow-up period of 70 days, when a dentin-like bridge was expected. In conclusion, the initial hypothesis was not confirmed.